Analysis of Pulp Capping Procedures Done in Permanent Molars in A University Setting - A Retrospective Study - Fahmida Binti Abd Rahman1 , M.S. Nivedhitha2, T.N.Uma Maheshwari3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Direct and indirect pulp capping are the treatment choices to maintain integrity and health of dental pulp.Direct pulp capping is used when pulp is visibly exposed due to caries, trauma or iatrogenic causes. Indirectpulp capping generally performed on teeth with deep cavity preparations with or without caries remaining.Many authors have reported regarding pulp capping materials. The aim of this retrospective study wasto analyse the practice of pulp capping procedure based on age, gender, tooth number and pulp cappingmaterials. Data regarding pulp capping procedures that were recorded between June 2019 to March 2020were retrieved from the patients management software of Saveetha Dental College, Chennai. Data thatwas retrieved then evaluated by 2 viewers. Cases with incomplete documentation or double entries wereexcluded from this study. Data from the Excel sheet was imported to SPSS for statistical analysis. Chisquare test was done to assess the association between age, gender, tooth types, type of pulp capping andpulp capping material. This study showed a statistically significant difference between age and tooth number;tooth number and pulp capping materials ( p<0.05). It was seen that lower molars underwent significantlymore pulp capping procedure in the age group of 18-30 years. In lower molars, calcium hydroxide was thewidely used pulp capping material.